Answer:
[tex]f\left(2,3,1\right)=\bold{14}[/tex]
Step-by-step explanation:
Given the function:
[tex]f\left(x,y,z\right)=\frac{x^3-2.5y^2+\frac{z}{2}}{z\left(x-y\right)}[/tex]
To find:
The value of [tex]f(2, 3, 1)[/tex] = ?
Solution:
[tex]f(2, 3, 1)[/tex] means the values of [tex]x, y\ and\ z[/tex] as:
[tex]x=2\\y=3\\z=1[/tex]
Let us put the given values in the given function and let us solve for it:
[tex]\Rightarrow f\left(2,3,1\right)=\dfrac{2^3-2.5\times 3^2+\frac{1}{2}}{1\left(2-3\right)}\\\\\Rightarrow f\left(2,3,1\right)=\dfrac{8-2.5\times 9+0.5}{1\left(-1\right)}\\\\\Rightarrow f\left(2,3,1\right)=\dfrac{8-22.5+0.5}{-1}\\\\\Rightarrow f\left(2,3,1\right)=\dfrac{-14}{-1}\\\\\Rightarrow f\left(2,3,1\right)=\bold{14}[/tex]
Therefore, the answer is:
[tex]f\left(2,3,1\right)=\bold{14}[/tex]